Efektivitas Aplikasi Amonium Klorida dan Sumber Kalium Berbeda pada Pertumbuhan dan Produksi Jagung Manis (Zea mays saccharata Sturt) - Ajang Christrianto; Lilik Tri Indriyati; Heru Bagus Pulunggono (Institut Pertanian Bogor, 2023)
Nitrogen (N) fertilizer of the urea type is very commonly used in Indonesia. The demand for this fertilizer is expected to increase, so an alternative is needed as a complement. Ammonium chloride (NH4Cl) is a by-product produced in the soda ash industry. This compound contains 26% N, which can be an alternative source of N nutrients for plants. The level of the following element, namely chlorine (Cl), is relatively high, so it is a concern that might affect the plant growth. This field experiment aimed to evaluate the effect of the application of ammonium chloride combined with potash fertilizers on the growth, production, and uptake of N and Cl nutrients in sweet corn plants. The trial was designed in a randomized group with nine treatments of 0%, 100%, 150%, and 200% N, combined with potassium sources from KCl and K2SO4. As a comparison, the source of N is urea at a dose of 100% N is referred to as the standard N treatment. Parameters observed included plant height, the weight of corn cobs and corn stover, N and Cl nutrient uptakes in seeds, leaves, and stems. The results showed that the application of ammonium chloride combined with different K sources markedly affected plant height, cob and plant stover weight, and N and Cl uptakes of sweet corn compared to controls. Applying N-ammonium chloride with KCl and K2SO4 showed no significant effect in growth and yield compared to standard N. The N dose showed no significant effect on plant growth and yield compared to the standard N dose. Keywords: by-product, nitrogen fertilizer, soda ash